1999
DOI: 10.1007/s007050050497
|View full text |Cite
|
Sign up to set email alerts
|

Complete nucleotide sequence and genomic organization of a primate calicivirus, Pan-1

Abstract: The primate calicivirus, Pan-1, was originally isolated from several primate species. It displayed typical calicivirus morphology by electron microscopy. We determined the genomic sequence of Pan-1 by cDNA cloning and direct RNA sequencing. Pan-1 shares a similar genomic organization and a high degree of sequence identity with feline caliciviruses. The Pan-1 genome contains 8,304 nucleotides, plus a poly-A tail, and is longer than any other calicivirus strains with a completely known sequence. The extra sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The complementary evidence for viremia included positive results from separate laboratories testing separate sample sets, utilization of RT-PCR assays that amplified non-overlapping genomic regions, direct detection of genomic RNA by hybridization, and amplicon sequencing that revealed non-identity of sequence compared with known Vesivirus, including strains characterized in one of the laboratories previously [Rinehart-Kim et al, 1999] and among the set of characterized amplicons themselves. These results together indicate that the positive laboratory results were not because of contamination in sample collection and handling.…”
Section: Discussionmentioning
confidence: 99%
“…The complementary evidence for viremia included positive results from separate laboratories testing separate sample sets, utilization of RT-PCR assays that amplified non-overlapping genomic regions, direct detection of genomic RNA by hybridization, and amplicon sequencing that revealed non-identity of sequence compared with known Vesivirus, including strains characterized in one of the laboratories previously [Rinehart-Kim et al, 1999] and among the set of characterized amplicons themselves. These results together indicate that the positive laboratory results were not because of contamination in sample collection and handling.…”
Section: Discussionmentioning
confidence: 99%
“…8) (17, 43). The amino acid similarity of these proteins ranges from 25 to 31% and represents one of the most divergent regions of polyprotein sequence within and between Caliciviridae genera (6,9,28,29). It was suggested that the RHDV 23-kDa protein might have functional similarity with the 2B protein of picornaviruses that alone or as a part of its precursor, 2BC, is involved in membrane modifications in virus-infected cells that include rearrangements and vesicle formation (4,40), change in membrane permeability (1,13), and disassembly of the Golgi complex (32).…”
Section: Discussionmentioning
confidence: 99%
“…Pan-1 originally was isolated from a pygmy chimpanzee (37). The three-dimensional structure of the Pan-1 virion and the sequence of the Pan-1 genome are known (28,31). Pan-1 grows to a high titer and causes cytopathic effects in monkey cell lines.…”
Section: Methodsmentioning
confidence: 99%